Keanekaragaman Serangga Nokturnal Di Komplek Pertamina Bagus Kuning Palembang - Miftahul Jannah; Siti Masruroh; Dwi Suci Wahyuni; Nia Arrizqi Alviani; Wiliaz Salsadiva; Aulia Asri; Yuniska Berliana; Anggun Wicaksono (Universitas Nusantara PGRI Kediri, 2023)
Studies on the diversity of nocturnal insects in the city of Palembang, especially in the Pertamina Bagus Kuning Complex, Palembang, are still limited, so it is necessary to carry out research on the diversity of nocturnal insects in the area. This study aims to determine the level of diversity of nocturnal insects active in the Pertamina Bagus Kuning Complex. This research was conducted in December 2022. This research was conducted using light traps as a place to catch nocturnal insects. The method used is a descriptive survey by direct observation of insects in the Pertamina Bagus Kuning Complex. The number of light traps used was 2 traps placed at 2 different stations, the light traps were placed at 18.00 WIB and collected the next day at 05.30 WIB. The results showed that nocturnal insects caught by light traps were 35 individuals from 8 species and 5 orders. The diversity of nocturnal insect species in the Pertamina Bagus Kuning Complex area based on Shannon-Weiner (H') of 1.74753679 is classified as moderate.